Midostaurin abrogates CD33‐directed UniCAR and CD33‐CD3 bispecific antibody therapy in acute myeloid leukaemia. (23rd May 2019) - Fasslrinner, Frederick; Arndt, Claudia; Koristka, Stefanie; Feldmann, Anja; Altmann, Heidi; von Bonin, Malte; Schmitz, Marc; Bornhäuser, Martin; Bachmann, Michael
Summary: Combinatory therapeutic approaches of different targeted therapies in acute myeloid leukaemia are currently under preclinical/early clinical investigation. To enhance anti‐tumour effects, we combined the tyrosine kinase inhibitor (TKI) midostaurin and T‐cell mediated immunotherapy directed against CD33. Clinically relevant concentrations of midostaurin abrogated T‐cell mediated cytotoxicity both after activation with bispecific antibodies and chimeric antigen receptor T cells. This information is of relevance for clinicians exploring T‐cell mediated immunotherapy in early clinical trials. Given the profound inhibition of T‐cell functionality and anti‐tumour activity, we recommend specific FLT3 TKIs for further clinical testing of combinatory approaches with T‐cell based immunotherapy.